Isomorphs of a class of Queueing systems - A. Ghosal; Sudhir Madan (International Journal of Mathematics and Mathematical Sciences)
Restricted isomorphism between two queueing systems implies that they have equivalent distribution function for at least one (but not all) output elements (e.g. waiting time, queue size, idle time, etc.). Quasi-isomorphism implies an approximate equivalence. Most of the single-server queueing systems can be approximated by a quasi-isomorphic system which has a gamma inter-arrival and gamma service distributions (Ep/Eq/1).